2018
DOI: 10.1038/s41467-018-07064-6
|View full text |Cite
|
Sign up to set email alerts
|

No significant boron in the hydrated mantle of most subducting slabs

Abstract: Boron has become the principle proxy for the release of seawater-derived fluids into arc volcanics, linked to cross-arc variations in boron content and isotopic ratio. Because all ocean floor serpentinites so far analysed are strongly enriched in boron, it is generally assumed that if the uppermost slab mantle is hydrated, it will also be enriched in boron. Here we present the first measurements of boron and boron isotopes in fast-spread oceanic gabbros in the Pacific, showing strong take-up of seawater-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Serpentinite breakdown has long been believed to play a crucial role in element transfer in subduction zones 8 , 15 , 16 . However, whether this serpentinite formed in the downgoing oceanic lithosphere or in the fore-arc mantle has been difficult to resolve 27 , 28 . Mo isotopes may help distinguish the respective roles of these two serpentinite sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serpentinite breakdown has long been believed to play a crucial role in element transfer in subduction zones 8 , 15 , 16 . However, whether this serpentinite formed in the downgoing oceanic lithosphere or in the fore-arc mantle has been difficult to resolve 27 , 28 . Mo isotopes may help distinguish the respective roles of these two serpentinite sources.…”
Section: Discussionmentioning
confidence: 99%
“…While the importance of serpentinite subduction in the subduction zone chemical cycle is now widely acknowledged, it remains a formidable task to discriminate among these competing models. Which serpentinite sources are responsible, and how they work in the subduction zones are still unclear 27 , 28 . Molybdenum (Mo) is mobile in fluids, like Pb and Ba, but it can also be partially retained in rutile during slab dehydration or melting.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the only plausible reason for B enrichment in the primary mantle minerals is supply of boron as the rocks still resided at mantle depth, providing for high enough temperatures to facilitate re‐equilibration. A possible scenario is that B‐enriched fluid was liberated by dehydration of abyssal serpentinite in a subducting footwall plate, which may contain up to 200 ppm B (Harvey et al., 2014; McCaig, 2018; Pabst et al., 2011; Vils et al., 2008). The released fluid, in turn, migrated to the overlying mantle wedge and re‐equilibrated with the mantle minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this close association with troctolites and an alteration texture typical for rodingitization, massive occurrence of clinopyroxene in the 400 °C experiment might provide an alternative low T formation hypothesis for this unique dyke lithology. Secondary clinopyroxene in association with altered troctolites has been reported before at Hess Deep where it was interpreted as a late high-grade (>360 °C) hydrothermal overprint of a preceding chlorite-prehnite alteration that occurred lower temperatures (200 °C -Gillis et al 2014;McCaig et al 2018).…”
mentioning
confidence: 70%
“…However, only few studies investigated the alteration of troctolitic rocks (Frost et al 2008;Beard et al 2009;Nakamura et al 2009;Nozaka et al 2017;McCaig et al 2018). Frost et al (2008) suggested that the troctolite alteration resembles a one-rock rodingitization, in which olivine represents the ultramafic and plagioclase the gabbroic component.…”
Section: Introductionmentioning
confidence: 99%